MINOR POLITICAL PARTIES IN ALLIANCES: AN ANALYTICAL STUDY OF PAKISTANI PARLIAMENTARY DEMOCRACY (1988-1999) - Pervez Akhter , Dr. Mazher Hussain , Dr. Khalil Ahmad; Pervez Akhter , Dr. Mazher Hussain , Dr. Khalil Ahmad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Pakistan was achieved on the basis of democratic and constitutional struggle. However, Pakistan faced lacking in emerging system which led a persistence sea saw of power. In parliamentary system, Minor parties have great extraordinary impact in politics. These are still playing role and also looking to play an increasingly important role. In 1988-99, Benazir and Nawaz Sharif comprehensively failed with causes of misuse of power and lacking of respect for the Constitution. The breakup of democratic rules had been challenged the political ideologies which led to social and governmental corruption. Democracy can never develop without common freedoms, justice, rule of law and equal opportunities. Political alliances are constituted momentarily in order to achieve particular target through joint endeavors. Literally, political Alliance means the confederation of numerous groups or political parties for the achievement of common objectives. The society factor played a role in the creation of Alliance. During the period of instability, the alliances continued in the Pakistan IJI and PDA play very vital and active role in the politics of Pakistan. COP, NDA and GDA were alliances which arranged a foundation stone of opposition. The role of Minor parties in political alliances re-energized its political activities but these activities contributed great to its finish. This research in hand highlights the performance of minor political parties and groups in making and breaking of political alliances.